Influencia de la comunicacion interna en el sentido de pertenencia de los colaboradores de la empresa l&s nassi sac - la esperanza. 2015 - Vera Inga, Keyla Greysi (2015)
The internal communication, he is her that he guides present I study, which allows me knowing how the influences the company collaborators' sense of possession and L&S NASSI SAC. With this study, he sought to know himself like the internal communication based in every day events and messages give motivational they influence the commitment, sentiment of rooting, pro-activity and the collaborators' identity. The case-study importance is found in the need that companies establishing adequate internal communication with their collaborators to develop in them their sentiment of possession and well-being and to increment the company productivity as well as the fulfillment of the entrepreneurial objectives. The present investigation centers its interest in the 35 collaborators' internal communication becoming manifest that spontaneity and improvisation make that communication is informal and influence the sentiment of possession negative already than limiter decrease the commitment, sentiment of rooting, pro-activity and the collaborators' identity.